ATAD5-BAZ1B interaction modulates PCNA ubiquitination during DNA repair - Yeongjae Kim; Na Young Ha; Mi-Sun Kang; Eunjin Ryu; Geunil Yi; Juyeong Yoo; Nalae Kang; Byung-Gyu Kim; Kyungjae Myung; Sukhyun Kang (Nature Communications)
Abstract Mono-ubiquitinated PCNA (mono-Ub-PCNA) is generated when replication forks encounter obstacles, enabling the bypass of DNA lesions. After resolving stalled forks, Ub-PCNA must be de-ubiquitinated to resume high-fidelity DNA synthesis. ATAD5, in cooperation with the UAF1-USP1 complex, is responsible for this de-ubiquitination. However, the precise regulation of timely Ub-PCNA de-ubiquitination remains unclear. Our research reveals that BAZ1B, a regulatory subunit of the BAZ1B-SMARCA5 chromatin-remodeling complex (also known as the WICH complex), plays a crucial role in fine-tuning the de-ubiquitination process of Ub-PCNA. The BAZ1B binding region of ATAD5 encompasses the UAF1-binding domain of ATAD5. Disruption of the ATAD5-BAZ1B interaction results in premature de-ubiquitination of Ub-PCNA following treatment with hydrogen peroxide. Cells with impaired BAZ1B binding to ATAD5 display increased sensitivity to oxidative stress compared to wild-type cells. These findings suggest that BAZ1B prevents premature Ub-PCNA de-ubiquitination, thereby safeguarding genome integrity.